Deverll & Hyde, Eds., The West In The History Of The Nation - A Reader - Arnold, David (Teaching History: A Journal of Methods, 2003)
The West in the History of the Nation is an excellent new primary source document collection that uses "western" examples to illuminate national themes-"western" with quotation marks, because much of the action in volume one takes place east of the one-hundredth meridian, where most western regionalists insist the "real West" begins. The two-volume set, which makes the standard break at Reconstruction, is intended primarily for accompaniment with the United States history survey course, but would also work quite well for courses on the American West.